Two Tax Receipts with Familiar Figures - Gonis, Nikolaos (Chronique d’Égypte, 2024)
Abstract Editions of two papyri from the British Library, each of which belongs to well-known clusters: the receipts for merismos paid by Makaris son of Kerekos at Kerkesoucha Orous, and the receipts for diagraphon paid by Kosma son of Proou, probably at Saqqara.